Prevalence, clinical features and emergency department blood pressure management of hypertensive emergencies and uncontrolled hypertension: a retrospective multi-centre study - Alessandro Maloberti; Giulia Capitoli; Tommaso Valobra; Paola Rebora; Nicolas Mavreas; Silvia Vergani; Valentina Giani; Chiara Tognola; Nicolò Capsoni; Michele Galasso; Lorenzo De Censi; Cecilia Ferretti; et al. (Hypertension Research, 2026)
Abstract Very heterogeneous data have been published concerning prevalence and clinical management of Hypertensive Emergencies (HE) and Uncontrolled Hypertension (UH). The aim of our study was to characterize HE and UH patients evaluating: (i) Blood Pressure (BP) management in Emergency Department (ED), the pharmacological treatment and its adherence to guidelines recommendation; (ii) variables associated with the presence of organ damage; and (iii), as an exploratory analysis, the impact of BP on in-hospital mortality. We performed a multicentre (Niguarda Hospital - Milan and Pio XI Hospital – Desio) retrospective study evaluating patients admitted to ED with BP values ≥ 180/120 mmHg during 2017 and 2019. 1838 patients were admitted to the ED with a BP ≥ 180/120 mmHg (0.95% of total admissions) of whom 37.7% were HE and the remaining (62.3%) were UH. The reduction in Systolic and Diastolic BP (SBP/DBP respectively) was similar in HE (40.6/16.9 ± 26.3/17.7 mmHg) and UH (39.3/15.5 ± 22.4/16.0 mmHg). The most used drugs were intravenous furosemide, nitroglycerin, clonidine and labetalol for HE. Age, smoking, heart failure, previous acute coronary syndrome, chronic kidney disease and diabetes mellitus present a positive association HEs while female sex and chronic anti-hypertensive therapies with 2 or more drugs results as protective variables. Finally, regarding the exploratory analysis, BP at ED admission and its management didn’t present significant association with in-hospital mortality. In conclusions, our study demonstrated that adherence to guidelines in the management of HE/UH could be further improved.